A Case of Necrotizing Fasciitis due to Streptococcus pneumoniae Serotype 5 in Saskatchewan - Meenakshi Dawar; Bob Russell; Karen McClean; Paul N Levett; Gregory J Tyrrell; James Irvine (Canadian Journal of Infectious Diseases and Medical Microbiology)
Necrotizing fasciitis due to Streptococcus pneumoniae is a rare and grave condition, and only a few cases have been reported. Suggested risk factors include minor trauma, systemic lupus erythematosus, immunosuppression secondary to medication, use of intramuscular anti-inflammatories and alcoholism. A fatal case of pneumococcal necrotizing fasciitis that occurred in a 51-year-old woman with a history of alcohol abuse and oral anti-inflammatory use is presented. Her condition was caused by a multi-etiology outbreak of community-acquired pneumonia, from which S pneumoniae serotype 5 was also isolated. The case description outlines the subtle presentation and rapid clinical progression of this condition. Because serotype 5 antigen is included in the polysaccharide 23-valent pneumococcal vaccine, the present case highlights the importance of pneumococcal immunization programs in Canada.